(untitled) (Антропологический форум / Forum for Anthropology and Culture, 2021)
This ‘Forum’ is devoted to recent changes in the institutional organisation of academic work and their consequences. The participants discuss the changed conditions for academic activity: the state science policy in various countries, the position of (young) colleagues in academy institutes and universities, the grant system and the work of researchers in short-term projects and research groups, the criteria by which the results of academic work and the scholar’s success are judged and the reliability of metrics, the divergence in positions and mutual distrust between academic administrators and researchers. The respondents indicate the most acute problems, and suggest solutions that might improve the present situation, and alternative schemes for organising academic work.